2003
DOI: 10.1024/0044-3514.34.4.219
|View full text |Cite
|
Sign up to set email alerts
|

The German Post-Critical Belief Scale: Internal and External Validity

Abstract: Recently, Duriez, Fontaine and Hutsebaut (2000) and Fontaine, Duriez, Luyten and Hutsebaut (2003) constructed the Post-Critical Belief Scale in order to measure the two religiosity dimensions along which Wulff (1991 , 1997 ) summarized the various possible approaches to religion: Exclusion vs. Inclusion of Transcendence and Literal vs. Symbolic. In the present article, the German version of this scale is presented. Results obtained in a heterogeneous German sample (N = 216) suggest that the internal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Before doing so, we wish to stress once more that, although all of the results that were described are based on multiple samples, most samples were gathered in Flanders (Belgium). However, whenever data from other countries are available as well (e.g., Duriez et al, 2003;, results appear cross-culturally valid. And although the Post-Critical Belies Scale was constructed for the use in a Christian context, initial data gathered with a modified scale among Belgian Muslims suggest that the results can also be generalized across denomination (Vancauwenberghe, Van Hiel & Duriez, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Before doing so, we wish to stress once more that, although all of the results that were described are based on multiple samples, most samples were gathered in Flanders (Belgium). However, whenever data from other countries are available as well (e.g., Duriez et al, 2003;, results appear cross-culturally valid. And although the Post-Critical Belies Scale was constructed for the use in a Christian context, initial data gathered with a modified scale among Belgian Muslims suggest that the results can also be generalized across denomination (Vancauwenberghe, Van Hiel & Duriez, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Following the reasoning of Schluderman et al (2003), it might be that, although being religious seems to go hand in hand with certain aspect of (right-wing) authoritarianism, it might not be related to those aspects of (right-wing) authoritarianism that predict racism and ethnic prejudice. Therefore, Duriez (2004a, Duriez, Appel & Hutsebaut, 2003 examined the relationship between religiosity and ethnic prejudice in more detail. Results show that Exclusion versus Inclusion is not related to ethnic prejudice.…”
Section: Religion and Ethnic Prejudicementioning
confidence: 99%
“…Using the PCBS, it has been demonstrated that two dimensions of religiosity predict different types of prejudice (Brandt and Van Tongeren ; Duriez ; Duriez, Appel, and Hutsebaut ; Shen et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…FA and SCA-ECP showed the existence of three factors (Hutsebaut, 1996;Krysinska et al, 2014), while PCA yielded two factors, with the Inclusion vs. Exclusion of Transcendence factor being better fitted in some samples than Literal vs. Symbolic (Bartczuk et al, 2013;Cortés Gómez et al, 2016;Duriez et al, 2003). MDS analyses, in contrast, showed the existence of four factors (Aguilar-Vafaie & Moghanloo, 2008;Bartczuk et al, 2011;Bartczuk et al, 2013;Cortés Gómez et al, 2016;Duriez et al, 2003;Duriez et al, 2000;Duriez et al, 2005;Fontaine et al, 2003).…”
Section: Problems With the Structure Of Attitudes Towards Religion In Previous Studiesmentioning
confidence: 99%
“…Symbolic (Bartczuk et al, 2013;Cortés Gómez et al, 2016;Duriez et al, 2003). MDS analyses, in contrast, showed the existence of four factors (Aguilar-Vafaie & Moghanloo, 2008;Bartczuk et al, 2011;Bartczuk et al, 2013;Cortés Gómez et al, 2016;Duriez et al, 2003;Duriez et al, 2000;Duriez et al, 2005;Fontaine et al, 2003).…”
Section: Problems With the Structure Of Attitudes Towards Religion In Previous Studiesmentioning
confidence: 99%